Assigning function to active site residues of Schistosoma mansoni thioredoxin/glutathione reductase from analysis of transient state reductive half-reactions with variant forms of the enzyme - Smith, Madison M.; Moran, Graham R. (Frontiers in Molecular Biosciences, 2023)
Flavoprotein disulfide reductase enzymes have been studied extensively for decades. However, relatively few studies employ transient-state methods combined with rigorous anaerobic technique to reveal chemical sequences. Eukaryotic glutathione reductase (GR), thioredoxin reductase (TrxR) and glutathione/thioredoxin reductase (TGR) are a structurally related set of enzymes that harvest electrons from NADPH to reduce disulfide substrates. Each has an FAD cofactor and internal disulfides that are presumed to act in an electron distribution role to pass electrons from the flavin to oxidant substrates. This article is the second article from our laboratory describing TGR. The first article (26) mapped chemical sequences that occur in U597C variant TGR as a facsimile of the WT enzyme. This study details functional assignment of five residues implicated to be involved in the chemistry catalyzed. These include residues participating in NADPH binding, thiol activation by deprotonation and one cysteine in each of the three proposed functional disulfides within this enzyme. The data for each variant is clear and in four of the five defines the role of the parent residue in catalysis. The analysis methods employed utilize three charge transfer absorption transitions that accumulate and decay in sequence in the reductive half-reaction of this enzyme. This is the first study of its type for TGR but has direct applicability and expands what is known of the function of GR and TrxR enzymes.